Detection of Markers on Runway and Conversion to 3D Information for Automatic Landing Using Computer Vision - เสนเพ็ง เมืองมล; รุจานุรักษ์ มิติ (Progress in Applied Science and Technology, 2016)
This research proposes the design and implementation of an automatic landing assistant system of fixed-wing unmanned aerial vehicle (UAV) using a computer vision. The researchers are using a camera attached to the UAVs for the estimation between the position and runway which has two majors. First, the detected left - right stripes of runway use Threshold and Hough Transform. Second, the detected green dot symbol on the runway use linear algorithm which is Homography and Direct Linear Transform for accurate comparison. The result of the detection of the white left - right stripes of runway found that a detected border of the runway as well and the results of the detection using the green dot symbol found that the result of the Homography algorithm near to real value more than Direct Linear Transform algorithms.